1
$\begingroup$

I want to compute the following limit: $$\lim_{n\to\infty} \frac{\left(\frac{e}{F_{n+1}}\right)^{F_{n+1}} F_{n+1}!}{\left(\frac{e}{F_n}\right)^{F_n} F_n!},$$

where $F_n$ is the $n$th Fibonacci number. The limit is easily computed by using Stirling's approximation $n! \simeq \sqrt{2\pi n} \left(\frac{n}{e}\right)^n$:

$$\lim_{n\to\infty} \frac{\left(\frac{e}{F_{n+1}}\right)^{F_{n+1}} F_{n+1}!}{\left(\frac{e}{F_n}\right)^{F_n} F_n!} = \lim_{n\to\infty} \frac{\left(\frac{e}{F_{n+1}}\right)^{F_{n+1}} \sqrt{2\pi F_{n+1}} \left(\frac{F_{n+1}}{e}\right)^{F_{n+1}}}{\left(\frac{e}{F_n}\right)^{F_n} \sqrt{2\pi F_n} \left(\frac{F_n}{e}\right)^{F_n}}\\=\lim_{n\to\infty}\sqrt{\frac{F_{n+1}}{F_n}}\\=\sqrt{\frac{1+\sqrt{5}}{2}}.$$

Is it possible to show this without using Stirling's approximation?

$\endgroup$
0
$\begingroup$

$$(\frac e{F_{n+1}})^{F_{n+1}}F_{n+1}!\over (\frac e{F_n})^{F_n}F_n!$$

$$=\frac {\frac {e^{F_{n+1}-F_n}}{F_{n+1}^{F_{n+1}}}\prod_{i=F_n+1}^{F_{n+1}}i}{1\over F_n^{F_n}}$$

$$=\frac {F_n^{F_n}}{F_{n+1}^{F_{n+1}}}e^{F_{n+1}-F_n}\prod_{i=F_n+1}^{F_{n+1}}i$$

$$=\left(\frac {F_n}{F_{n+1}}\right)^{F_n}\prod_{i=F_n+1}^{F_{n+1}}\frac {ei}{F_{n+1}}\tag 1$$

Taking what we know: $F_{n+1}=F_n+F_{n-1},\ (1)$ becomes

$$\left(\frac {F_n}{F_n+F_{n-1}}\right)^{F_n}\cdot\prod_{i=F_n+1}^{F_n+F_{n-1}}\frac {ei}{F_n+F_{n-1}}$$

$$=e\left(\frac {F_n}{F_n+F_{n-1}}\right)^{F_n}\cdot\prod_{i=1}^{F_{n-1}-1}\frac {e(i+F_n)}{F_n+F_{n-1}}$$

I don't see anything that makes it much easier from here, except to note that

$$\left(\frac {F_n}{F_{n+1}}\right)^{F_n}\to \left(\frac {\sqrt 5-1}{2}\right)^{F_n}\to \frac 1{\left(\frac {1+\sqrt 5}2\right)F_n+F_{n-1}}$$

At the end of all this, that product is still waiting, and probably just needs Stirling's Approximation to complete the evaluation.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.